Sirtuin-2 Protects Neural Cells from Oxidative Stress and Is Elevated in Neurodegeneration - Preeti Singh; Peter S. Hanson; Christopher M. Morris (Parkinson's Disease)
Sirtuins are highly conserved lysine deacetylases involved in ageing, energy production, and lifespan extension. The mammalian SIRT2 has been implicated in Parkinson’s disease (PD) where studies suggest SIRT2 promotes neurodegeneration. We therefore evaluated the effects of SIRT2 manipulation in toxin treated SH-SY5Y cells and determined the expression and activity of SIRT2 in postmortem brain tissue from patients with PD. SH-SY5Y viability in response to oxidative stress induced by diquat or rotenone was measured following SIRT2 overexpression or inhibition of deacetylase activity, along with α-synuclein aggregation. SIRT2 in human tissues was evaluated using Western blotting, immunohistochemistry, and fluorometric activity assays. In SH-SY5Y cells, elevated SIRT2 protected cells from rotenone or diquat induced cell death and enzymatic inhibition of SIRT2 enhanced cell death. SIRT2 protection was mediated, in part, through elevated SOD2 expression. SIRT2 reduced the formation of α-synuclein aggregates but showed minimal colocalisation with α-synuclein. In postmortem PD brain tissue, SIRT2 activity was elevated compared to controls but also elevated in other neurodegenerative disorders. Results from both in vitro work and brain tissue suggest that SIRT2 is necessary for protection against oxidative stress and higher SIRT2 activity in PD brain may be a compensatory mechanism to combat neuronal stress.